2014
DOI: 10.1186/1471-2334-14-175
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic characterization of 30 confirmed cases of human infection with avian influenza A(H7N9) virus in Hangzhou, China

Abstract: BackgroundWe examined the clinical and epidemiological characteristics of 30 cases of human infection with avian influenza A(H7N9) virus in Hangzhou and investigated their external environments to provide evidence for contact tracing and disease prevention and control.MethodsThe cases confirmed from April 1 through May 1, 2013 were studied. Field epidemiologic surveys were conducted to collect the clinical and epidemiologic data. Case-related and environmental specimens were collected for etiologic detection.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…These findings are consistent with those of other published reports. [ 9 , 10 , 26 , 27 ] The atypical symptoms recorded during the early stage of A (H7N9) patients were noteworthy. Two elderly patients were hospitalized due to neurological syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with those of other published reports. [ 9 , 10 , 26 , 27 ] The atypical symptoms recorded during the early stage of A (H7N9) patients were noteworthy. Two elderly patients were hospitalized due to neurological syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen patients (56 %) had died. This death rate was much higher than that of other areas, which ranged from 10 % in Hangzhou city [ 9 ] to 39.4 % in Shanghai [ 10 ]. This is of particular concern, as Guangzhou is a highly developed city in China with an advanced medical infrastructure, and the HA and NA sequences of the H7N9 viral isolates from Guangzhou patients are identical to those of H7N9 virus strains recently isolated from human patients in other areas (A/Anhui/1/2013, A/Shanghai/1/2013).…”
Section: Introductionmentioning
confidence: 87%
“…Interestingly, two-thirds of the infected individuals have been male 19, 20, 2224, 2729 (Figure 2C). The high number of cases among elderly men may reflect socio-economical differences among age groups and genders since elderly men may have frequent work-related or non-job-related contact with poultry.…”
Section: Epidemiology Of Human H7n9 Virus Infectionsmentioning
confidence: 99%
“…It has been demonstrated that exposure to poultry in live poultry markets (LPMs) is strongly associated with human infections of avian influenza virus (AIV) subtype A(H7N9) 1 . In Hangzhou, the capital city of Zhejiang province, China, the first outbreak of human A(H7N9) infections emerged in April 2013 and was halted soon after the closure of LPMs in the main districts of the city 2 , 3 . These LPMs were reopened at the end of June 2013.…”
mentioning
confidence: 99%